МАСОФАВИЙ ТАЪЛИМ ШАРОИТИДА ПЕДАГОГЛАРНИ АКТ БЎЙИЧА МАЛАКАСИНИ ОШИРИШДА ИНДИВИДУАЛЛАШТИРИШ МУАММОЛАРИ - Ибадуллаева Зарнигор Оллаяр қизи (World Scientific Research Journal, 2025)
Annotation: In order to overcome the problems of professional development of teachers, in our opinion, not only the development of traditional organizational and pedagogical measures, but also step-by-step, categorical, industry-oriented, individualized methods, approaches, teaching models (distance learning, ON- LINE-learning).